Design and Optimization of Passive UHF RFID Systems - Curty, Jari-Pascal; Declercq, Michel; Dehollain, Catherine; Joehl, Norbert (Springer US : Imprint: Springer, 2007)
Radio Frequency Identification (RFID) is an automatic identification method, relying on storing and remotely retrieving data using devices called RFID tags or transponders. An RFID tag is an object that can be attached to or incorporated into a product, animal, or person for the purpose of identification using radio waves. Chip-based RFID tags contain silicon chips and antennas. Active tags require an internal power source, while passive tags do not. Design and Optimization of UHF RFID Systems considers the analysis, design and optimization of UHF passive RFID systems for long-range applications. There are many key aspects thoroughly described in the text: Wireless power transmission Tag-to-reader backscattering communication Reader and tag architectures and IC design. Wireless power transmission is studied using a rectifier (a fundamental tag building-block) for which there has been a proven prediction model developed. Proposed is a theoretical analysis of possible backscattering modulations, as well as an experimental procedure to measure how the impedance modulation at the tag side, affects the signal at the reader. Finally, a complete tag design achieving a read range of 12 m at 2.45 GHz (4 W EIRP) is provided. At the time of writing, the results of this design outperform any other available IC tag.